EFFECT OF WATER SOLUIBLE FRACTION (WSF) OF CRUDE OIL ON SOME BIOCHEMICAL CHARACTERS OF JUVENILES COMMON CARP, Cyprinus carpio L. - Abbas A. Hantoush; Ali M. Nasir (Basrah Journal of Veterinary Research)
This study was carried out juveniles common carp, Cyprinus carpio to determined the effect of (WSF) of crude oil on blood glucose and hemoglobin of blood values and glycogen of liver and muscles exposed to sub lethal effects for using different concentration. Study showed lower levels of blood hemoglobin and glycogen of liver and muscles, while blood glucose values have risen when exposed to concentrations of crude oil used.